Dapingian to lower Darriwilian (Middle Ordovician) graptolite biostratigraphy and correlation of the Krapperup drill core, Scania, Sweden. (2nd January 2021) - Maletz, Jörg; Ahlberg, Per
ABSTRACT: The Dapingian and lower Darriwilian graptolite succession of the Krapperup drill core from Scania, southern Sweden, provides a detailed insight into the axonophoran (biserial) graptolites and their early Palaeozoic evolutionary changes on the Scandinavian platform. Even though earliest Darriwilian axonophorans are not represented, the succession includes faunal elements of the basal Darriwilian Arienigraptus zhejiangensis Subzone of the Levisograptus austrodentatus Biozone, followed by Levisograptus mui and Levisograptus sinicus specimens higher up in the successsion. The highest interval is referred to the Eoglyptograptus cumbrensis Biozone and bears a number of axonophoran elements, including Oelandograptus oelandicus and Undulograptus camptochilus, previously known exclusively from chemically isolated material from the island of Öland. The top of the interval investigated is below the base of a carbonate-rich interval correlated with the Komstad Limestone of Scania, indicating that the investigated interval entirely belongs to the upper part of the Tøyen Shale Formation. Pseudisograptus manubriatus and Pseudisograptus koi are not restricted to the upper Dapingian, but range into the basal Darriwilian. Arienigraptus robustus n. sp. from the uppermost Dapingian, and Arienigraptus delicatus n. sp. and Arienigraptus balticus n. sp. from the basal Darriwilian, are described as new species.